?MONITORING THE QUALITY OF SUNFLOWER SEED BEFORE AND DURING STORAGE (Biological Sciences - PJSIR, 1996)
Storage life of sunflower seed can be increased by monitoring the quality of seed before and during the storageperiod. Cold test, accelerated and modified accelerated aging test, in which several germination tests were made overtime were evaluated. Modified accelerated aging test was found to be a more reliable method of seed quality evaluation.Seed lots having P50 viability period (period when germination drops to 50%) of 3.5 and above could be storedsafely upto one year in conducive environmental conditions.